Social identity differentiation predicts commitment to sobriety and wellbeing in residents of therapeutic communities. (September 2019) - Dingle, Genevieve A.; Haslam, Catherine; Best, David; Chan, Gary; Staiger, Petra K.; Savic, Michael; Beckwith, Melinda; Mackenzie, Jock; Bathish, Ramez; Lubman, Dan I.
Abstract: Rationale: Therapeutic communities (TC) for alcohol and other drug treatment rely strongly on social factors as agents of recovery; an approach known as 'community-as-method'. This study adopted a social identity approach in examining the relative strength of participants' recovery group identity and substance using group identity at admission (T1) and after six months (T2) in a TC. Objectives: Were to investigate whether identity differentiation – the extent to which respondents see themselves more as belonging to recovery groups than belonging to substance using groups – (a) is related to individuals' primary substance of concern (i.e., amphetamine type stimulants; alcohol; other drugs), and (b) predicts positive indicators of recovery six months after entering a therapeutic community. Method: Adults (N = 307) entering one of five Australian therapeutic communities (TC) completed measures of identification (user, recovery), commitment to sobriety, psychological distress, and personal wellbeing. Results: Participants' endorsement of the user and recovery identity at T1 and T2 did not differ as a function of primary substance of concern. User identity diminished over the six months while recovery identity remained high, regardless of primary drug category. Identity differentiation measured at T2 accounted for 20–25% variance in commitment to sobriety and wellbeing, after accounting for participant demographics, addiction severity, and T1 identity variables. Conclusions: These findings highlight the importance of the relative strength of recovery over substance use related identities in supporting recovery indicators and the central role of the TC in supporting this trajectory. Highlights: Study examined user and recovery identification in therapeutic community residents. Identity differentiation at six months predicted commitment to sobriety. Identity differentiation also predicted wellbeing and lower psychological distress. User and recovery identity ratings were unrelated to primary substance of concern.